2018
DOI: 10.3390/su10072114
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Word of Mouth on Tourism Destination Choice: Tourist–Resident Relationship and Safety Perception among Mainland Chinese Tourists Visiting Macau

Abstract: The growth of urban tourism has the potential to increase tourist-resident tensions that limit the sustainable growth of tourism in many destination cities. Visitors' perceptions of poor tourist-resident relationships and conditions of safety may have an impact on their attitudes, especially with regard to trip satisfaction. This study investigates the roles of tourist-resident relationship and safety perception on the relationship between service quality, trip satisfaction, and word of mouth (WOM). The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 78 publications
(88 reference statements)
1
39
0
2
Order By: Relevance
“…Various authors have already pointed out the need for local authenticity through actions such as local gastronomic experiences, in order to achieve a more credible rural tourism product [23,[94][95][96]. Similarly, as recently noted by [97] (p. 1), "the tourist-resident relationship is one of the sustainability issues regarding the social aspect of tourism development". Therefore, it will be vital for the villages to retain their population, maintain their traditional functions, and involve the local population in tourism-related activities through social and cultural recreation.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have already pointed out the need for local authenticity through actions such as local gastronomic experiences, in order to achieve a more credible rural tourism product [23,[94][95][96]. Similarly, as recently noted by [97] (p. 1), "the tourist-resident relationship is one of the sustainability issues regarding the social aspect of tourism development". Therefore, it will be vital for the villages to retain their population, maintain their traditional functions, and involve the local population in tourism-related activities through social and cultural recreation.…”
Section: Discussionmentioning
confidence: 99%
“…Word-of-mouth (WOM) represents a form of communication among consumers who share their own stories and evaluations of products, services, brands or consumption experiences, in which the sources are considered independent of commercial influence (Oliver, 2010;Litvin et al, 2008). It plays a primary role in consumer behaviour as it includes sharing opinions and different reactions among consumers (Ka Wai Lai et al, 2018). In this way, the main dimension which differentiates word-of-mouth from other forms of marketing communication is interpersonality (Fili & Križaj, 2016).…”
Section: Wom -A Form Of Interpersonal Influence In Tourismmentioning
confidence: 99%
“…In the field of research on tourism safety, perceived safety refers to tourists' subjective feeling of the safety situation of the destination [17][18][19]. Numerous studies have shown that tourists' perceived safety of a destination significantly impacts on their decision-making [20][21][22]. In many destinations, the real risk has a limited impact, whereas tourists' subjective perceived safety plays a dominant role in the process of their decision-making [7,[23][24][25].…”
Section: Perceived Safetymentioning
confidence: 99%